After-Hours Block Trading, Short Sales, And Information Leakage: Evidence From Korea - Lee, Taehoon; Jun, Sang-gyung (Journal of Applied Business Research, 2017)
We investigate the impact of insider trading in after-hours block market on stock price and short sales volume, before and after the trading becomes public information. During pre-announcement period, positive (negative) abnormal stock return is generated when insiders buy (sell) their shares but does not when quasi-insiders trade, implying that stock price reflects long-lived private information of corporate governance structure. The impact is most prominent when ownership shares are transferred to (from) corporate insiders. In contrast, short sales volume generally does not depend on the identity of block holders. Short sales volume has a negative correlation with abnormal stock return only during the transaction date, indicating that a short-sale decision of tippees is based on their sole expectation on instantaneous stock returns. We also find evidence that insiders select the timing of their trades with respect to maximizing their realized profits or minimizing their purchasing costs.
Keywords: After-Hours Block Trading; Corporate Governance Structure; Insider Trading; Short Sales; Information Leakage